Strategi Pengembangan Diri Agen Asuransi Dalam Mencapai Target pada PT. Sunlife Financial Cabang Kota Medan - Nasution, Alya Mahpuja; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the agent's self-development strategy in achieving the target. At PT. Sunlife Financial Medan city branch. This research data uses qualitative or descriptive methods through interviews, observations and data provided by related companies. In achieving the targets set by the company, agents are given special training by the company in developing themselves to become good and correct agents in marketing their products, deepen themselves to know about insurance products, and learn about techniques to attract customers' interest, as well as learn how to maintain customers to continue to be customers of PT. Sunlife Financial Medan city branch.